Does Body Composition and Weight Influence an Individual's Perception of Ideal Body Shape? - Majid Donyaei; Kuroush Jafarian; Jalal Hejazi (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: An individual's attitude toward an ideal body can affect different aspects of their life. There is no clear evidence regarding the relationship between an individual's body composition and ideal body image. The aim of the present study was to determine the relationship between an individual's body fat percent and weight on his/her perception of ideal body shape. Materials and Methods: In this cross-sectional study, 151 volunteers who were referred to a diet therapy clinic in Tehran in 2016 participated. Participants were selected by convenience sampling method. At first, weight, height and body composition of participants were measured. Then, 21 standardized female body images with different waist to hip ratios (WHR) and body fat percent (BF%) were presented to the participants. The participants were asked to rank them according to their attractiveness. Then the images were scored according to their ranks and the trend of score changes in the different levels of studied factors was evaluated. Data were analyzed in SPSS-22 software using descriptive methods, analytical tests such as repeated measure analysis of variances, Bonferroni and linear regression. Results:  A total of 151 people, including 92 (60.9%) women and 59 (39.1) men participated in the study. The image with WHR of 0.68 and BF% of 23% received the highest score (8 out of 9). A linear inverse relationship was found between the score of the image and its WHR (P< 0.001) and BF% (P<0.001). The interaction between WHR and BF% was also significant (P< 0.001). No significant differences were found between the scores of individuals with different levels of BMI, body fat and gender. Conclusion: Study showed factors such as gender, weight and body composition have no effects on the ideal body image perception.